MIS: mommies information system - Kasim, Shahreen; Mohamed Shareef, Siti Hawa; Wahid, Norfaradilla; Hafit, Hanayanti (Penerbit UTHM, 2017)
Internet and Internet of Things is very popular nowadays with various services related to many different fields. Internet is a truly versatile and help in solving many tasks easily by browsing the links available (O’brien, 2014). In the present technology, the Internet has grown to be a medium to deliver information quickly with network connectivity to users (Xia et al., 2012). Diary-based website is an engineering innovation where the diary can be accessed through the Website, which is a combination of pages contained in a domain or subdomain that are in the World Wide Web (WWW) on the Internet and subsequently displayed to the user via a web browser (Liu & Arnett, 2000). Development of diary based website has much to offer to the clinical world where it offers easily-accessible electronic medical records to the patients as wells as to the medical organizers.